Impacts of Teratosphaeria leaf disease on plantation Eucalyptus globulus productivity. Issue 2 (30th November 2016) - Smith, A.H.; Wardlaw, T.J.; Pinkard, E.A.; Ratkowsky, D.; Mohammed, C.L.
Summary: The effects of Teratosphaeria leaf disease (TLD) on Eucalyptus globulus are varied, and it is currently poorly understood whether infection by TLD can cause long‐term growth effects. Such information would greatly assist disease management and pruning regimes on E . globulus plantation sites, resulting in both financial and ecological benefits. Two trials were established to quantify the effects of TLD on long‐term growth. The first was a 2‐year fungicide exclusion trial that aimed to determine initial growth losses between trees treated with fungicide and untreated trees. It was found that tree growth was not affected until a threshold value of 20% damage was reached. Volume was reduced by 17% between treated and untreated trees over the course of the 2‐year trial. The second trial, a 5‐year growth study, used differentially affected adjacent stands (one infected and the other unaffected) to look at the longer term effects of more severe defoliation (44–60%) caused by an epidemic of TLD. Results recorded 5 years after the epidemic showed that trees recovered to regain normal growth trajectories after the epidemic, but growth was retarded by ca. 1.2 years for both height and diameter compared with that of the adjoining unaffected stand. As the growth of trees was not permanently reduced by the epidemic, it is concluded that the financial impacts of TLD are more likely to be associated with the loss of income resulting from extensive branch death in the lower crown after leaf and stem infection, which makes the affected stands not suitable for pruning and hence prevents them from being managed as a higher value solid wood crop.